A chemical‐absorption heat pump for utilization of nuclear power in high temperature industrial processes. (23rd April 2021) - Armatis, Paul D.; Gupta, Aman; Sabharwall, Piyush; Utgikar, Vivek; Fronk, Brian M.
Summary: This study investigates the technical feasibility and quantifies the technical potential of using a chemical‐absorption heat pump to upgrade thermal energy from nuclear reactors to be used for high temperature thermal processes. Presently, high temperature industrial process heat is produced on‐site through combustion of fossil fuels or use of grid electricity by resistance heating. These two methods either generate significant amounts of greenhouse gas emissions or waste large amounts of energy through multiple thermal‐electrical conversions. Co‐location of a small modular reactor (SMR) and an industrial thermal process can significantly improve energy efficiency with less carbon emissions. Chemical heat pumps can be used to create a thermal pathway between the nuclear reactor and the industrial process when there is a temperature mismatch. In this work, we present a calcium oxide hydration reaction based chemical heat pump paired with a lithium bromide‐water absorption cycle to efficiently boost heat from a nuclear reactor for high temperature thermal processes. A steady state thermodynamic analysis reveals second law efficiencies above 0.7 for input temperatures of 325°C to 375°C and output temperatures from 500°C to 800°C. The system size is greatly dependent on the dehydration temperature from the nuclear reactor and pressure drop between the dehydration bed and LiBr ‐ H2 O absorber. Abstract : A novel absorption cycle assisted chemical heat pump is proposed and evaluated. The system receives medium grade heat (300°C‐400°C) and delivers high‐grade heat (500°C‐800°C) for industrial process heating. This system has potential to significantly reduce the energy used for industrial processes by upgrading heat and avoiding costly energy conversions.